A phase 2 study of lenalidomide, rituximab, cyclophosphamide, and dexamethasone (LR‐CD) for untreated low‐grade non‐Hodgkin lymphoma requiring therapy. Issue 5 (22nd March 2017) - Rosenthal, Allison; Dueck, Amylou C.; Ansell, Stephen; Gano, Katherine; Conley, Christopher; Nowakowski, Grzegorz S.; Camoriano, John; Leis, Jose F.; Mikhael, Joseph R.; Keith Stewart, A.; Inwards, David; Dingli, David; et al.
Abstract: Patients with indolent non‐Hodgkin lymphoma (NHL) have multiple treatment options yet there is no consensus as to the best initial therapy. Lenalidomide, an immunomodulatory agent, has single agent activity in relapsed lymphoma. This trial was conducted to assess feasibility, efficacy, and safety of adding lenalidomide to rituximab, cyclophosphamide, and dexamethasone (LR‐CD) in untreated indolent NHL patients requiring therapy. This was a single institution phase II trial. Treatment consisted of IV rituximab 375 mg/m 2 day 1; oral lenalidomide 20 mg days 1–21; cyclophosphamide 250 mg/m 2 days 1, 8, and 15; and dexamethasone 40 mg days 1, 8, 15, and 22 of a 28‐day cycle. Treatment continued 2 cycles beyond best response for a maximum of 12 cycles without rituximab maintenance. Thirty‐three patients were treated. Median age was 68 (43–83 years). 39% had stage IV disease. Histologic subtypes included 8 follicular lymphoma (FL), 7 marginal zone lymphoma (MZL) (1 splenic, 2 extranodal, and 4 nodal), 15 Waldenström's macroglobulinemia (WM), 1 lymphoplasmacytic lymphoma, 1 small lymphocytic lymphoma, and 1 low‐grade B‐cell lymphoma with plasmacytic differentiation (unable to be classified better as MZL or LPL). Hematologic toxicity was the most common adverse event. Median time of follow‐up was 23.4 months (range 1.8–50.9). The overall response rate was 87.9%, with 30.3% complete response. The median duration of response was 38.7 months. The median progression free survival was 39.7 months, while median overall survival (OS) has not yet been reached. Lenalidomide can be safely added to a simple regimen of rituximab, oral cyclophosphamide, and dexamethasone and is an effective combination as initial therapy for low‐grade B‐cell NHL.